Determinan Kinerja UMK Batik Berdasarkan Orientasi Kewirausahaan, Budaya Organisasi, dan Faktor Internal - Irmawati, Irmawati; Hidayah, Khusnul (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2023)
Small Micro Enterprises (SMEs) are one of the priorities for economic development in Indonesia because they are proven to be able to absorb labor and contribute to a large GDP amid the downturn due to the COVID-19 pandemic. The number of batik SMEs in Yogyakarta is increasing from year to year so business actors are required to think creatively and innovatively to face business competition and dynamic market conditions. The results showed that organizational culture variables had a positive and significant effect on the performance of batik MSEs in Yogyakarta. While the entrepreneurial orientation variables and internal factor variables have no effect on the performance of batik MSEs in Yogyakarta. This shows that the courage to take risks described in the entrepreneurial orientation and internal factors has not affected the performance of MSE Batik in Yogyakarta.